Mercouri G. Kanatzidis: Excellence and Innovations in Inorganic and Solid-State Chemistry - Arachchige, Indika U.; Armatas, Gerasimos S.; Biswas, Kanishka; Subrahmanyam, Kota S.; Latturner, Susan; Malliakas, Christos D.; Manos, Manolis J.; Oh, Youngtak; Polychronopoulou, Kyriaki; Poudeu, Pierre F. P.; Trikalitis, Pantelis N.; Zhang, Qichun; et al. (AMER CHEMICAL SOC, 2017)
Over the last 3-4 decades, solid-state chemistry has emerged as the forefront of materials design and development. The field has revolutionized into a multidisciplinary subject and matured with a scope of new synthetic strategies, new challenges, and opportunities. Understanding the structure is very crucial in the design of appropriate materials for desired applications. Professor Mercouri G. Kanatzidis has encountered both challenges and opportunities during the course of the discovery of many novel materials. Throughout his scientific career, Mercouri and his group discovered several inorganic compounds and pioneered structure-property relationships. We, a few Ph.D. and postdoctoral students, celebrate his 60th birthday by providing a Viewpoint summarizing his contributions to inorganic solid-state chemistry. The topics discussed here are of significant interest to various scientific communities ranging from condensed matter to green energy production.
Keywords: HIGH THERMOELECTRIC FIGURE; CHARGE-DENSITY-WAVE; SENSITIZED SOLAR-CELLS; MESOSTRUCTURED SEMICONDUCTORS; BIOMIMETIC CHALCOGELS; MESOPOROUS GERMANIUM; RADIATION DETECTION; ALUMINUM SILICIDES; THERMAL-EXPANSION; MOLTEN ALUMINUM